Protection and Prevention Approaches in Occupational Health and Safety (IntechOpen, 2025)
Developments in working life have also brought about occupational health and safety (OHS) problems. While the development of technology and protective equipment has created a safer working environment over time, new risks that pose a danger have also emerged. OHS aims to prevent the deterioration of employees' health in all occupational groups, protect employees from the hazards and risks in the environment, and provide environments that will allow individuals to continue to work at the highest level physiologically and spiritually. To create an OHS culture, it is not enough to simply explain the importance of the subject to employees and society. In order to transform this awareness into behavior, more emphasis and importance should be given to resources that will ensure that employees act by OSH rules during all their activities. OHS is considered an important public health problem today, and the first thing that needs to be done to prevent occupational accidents and diseases is to maximize the current knowledge of all parties involved on this subject. Education in the context of occupational safety and health is designed to provide employees with knowledge and skills so that managers and employees in the business can recognize the risk factors that may cause work accidents, injuries and diseases and be prepared for the damages that may occur in their work environments. This book aims to contribute to the training of experts working on occupational health and safety, which is the intersection of many different disciplines, in light of up-to-date information on this subject. It also provides a resource that employees can always benefit from regarding workplace protection and prevention.